2006
DOI: 10.1345/aph.1g437
|View full text |Cite
|
Sign up to set email alerts
|

Appeals System and Its Outcomes in National Health Insurance in Taiwan

Abstract: Most appeals were again denied after expert review. Better education concerning utilization guidelines and a platform for insurer, insuree, and physician to dialog are needed to improve the effectiveness and efficiency of the appeals system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, in most of the dementias, the etiology remained unclear. Even with cognitive enhancers, such as the acetylcholinesterase inhibitors, or the N-methyl D-aspartate (NMDA)-receptor antagonist, which might alleviate cognitive impairments, the cognitive decline, as well as the behavioral and psychological symptoms, are still a heavy burden for the dementia patients and their caregivers and their community (Fuh & Wang, 2008; S. J. Lin, Kuo, & Yang, 2006; Tzeng et al, 2015; Tzeng et al, 2017; H.Y.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the dementias, the etiology remained unclear. Even with cognitive enhancers, such as the acetylcholinesterase inhibitors, or the N-methyl D-aspartate (NMDA)-receptor antagonist, which might alleviate cognitive impairments, the cognitive decline, as well as the behavioral and psychological symptoms, are still a heavy burden for the dementia patients and their caregivers and their community (Fuh & Wang, 2008; S. J. Lin, Kuo, & Yang, 2006; Tzeng et al, 2015; Tzeng et al, 2017; H.Y.…”
Section: Introductionmentioning
confidence: 99%
“…Donepezil, was the first drug approved by NHI for treatment of mild to moderate AD patients. According to the latest reimbursement criteria, prior authorization is required for all new patients; furthermore, patients are evaluated every 6 months after initiating treatment (Lin et al, 2006). Patients who show either a decrease in Mini-mental state examination (MMSE) of 2 or more points or an increase in Clinical Dementia Rating (CDR) of one or more points on the rating scale during follow-up evaluation, reimbursement stops.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, 4.97% of those older than 65 years had dementia,1 which is a heavy burden to carry for the family members of patients with dementia and their caregivers and community, and the society as a whole 2–5. Previous studies had found that the human immunodeficiency virus (HIV) infections were associated with HIV-associated neurocognitive disorders (HAND)6 and HIV-associated dementia (HAD) 7.…”
Section: Introductionmentioning
confidence: 99%